Korelasi Antara Aktivitas Sehari-hari Ibu Rumah Tangga dengan Kejadian Carpal Tunnel Syndrome di RS Toeloengredjo Pare Kediri - Siti Munasaroh; Wiek Israwan; Amin Zakaria; Fransisca Xaveria Hargiani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Carpal tunnel syndrome (CTS) is a syndrome caused by compression of the median nerve in the carpal tunnel in the wrist. Symptoms include pain, numbness, and paresthesia. CTS is common in women, 9.2% in women, 8% in men with the highest outcome being housewife.Methods: This study uses a quantitative cross-sectional design, the approach is observational. The sampling technique was purposive sampling, the number of studies was 30 housewife patients with carpal tunnel syndrome at the Physiotherapy Polyclinic, Toeloengredjo Hospital, Pare, Kediri. This study was conducted by giving informed consent and questionnaires to housewife with CTS. Statistical test using the chi-squere test.Results: The results of the chi-square test were obtained from 30 respondents with an average age of 51.70 years, the results of repetitive motion with the phalen test were 0.030% (p<0.05%), the results of repetitive motion with CTS pain were 0.00% (p<0, 05), repetitive motion with CTS criteria 0.000% (p<0.05). This shows that there is a correlation between the activities of housewife and the incidence of CTS.Conclusion: There is a correlation between age, hand pain, and repetitive movement with the incidence of Carpal Tunnel Syndrome in the daily activities of housewife. The correlation between age and the incidence of CTS, the older the age, the more at risk of CTS. The correlation between repetitive motion and CTS criteria is the heaviest value due to manual washing of clothes every day, the heavier the load, the greater the risk of CTS.